Length–weight and length–length relationships for 11 species of the genus Alburnoides Jeitteles, 1861 (Cyprinidae) from Iran. (30th January 2017) - Mousavi‐Sabet, H.; Heidari, A.; Vatandoust, S.
Summary: Length–weight (LWR) and length–length (LLR) relationships were estimated for 11 Alburnoides species from 15 localities throughout Iran. These represent the first reports of LWR and LLRs data for 10 species, including: Alburnoides coadi (40 specimens), A. damghani (30), A. eichwaldii (110), A. holciki (30), A. idigensis (113), A. namaki (30), A. nicolausi (30), A. parhami (30), A. qanati (30) and A. tabarestanensis (30) and first LLR data for A. samiii . Nine of these species are endemic and two are native to Iran. The length–weight parameter b for these species ranged from a minimum of 2.94 for Alburnoides nicolausi to a maximum of 3.37 for Alburnoides parhami, with regression coefficients ( r 2 ) ranging from 0.91 to 0.99. All LLRs were highly significant ( r 2 > 0.96).